The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1039/c5ra01461a
|View full text |Cite
|
Sign up to set email alerts
|

Pd–imidate complexes as recyclable catalysts for the synthesis of C5-alkenylated pyrimidine nucleosides via Heck cross-coupling reaction

Abstract: Pd–imidate complexes as recyclable catalysts for Heck alkenylation of pyrimidine nucleosides. Pd–imidate complexes have been employed as efficient catalysts for the Heck alkenylation of unprotected 5-iodo-2′-deoxyuridine in acetonitrile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
(7 reference statements)
0
20
0
Order By: Relevance
“…In a collaborative effort with the Serrano group, PTA based palladium complexes were synthesized and screened for the catalytic cross-coupling of nucleoside in water. In this study, the first set of [Pd(imidate) 2 (PTA) 2 ] were synthesized and found to exhibit appreciable water-solubility (110 mg/mL) [37,51]. The titled complexes can be easily synthesized by the reaction between trans-[Pd(imidate) 2 (SMe 2 ) 2 ] and PTA ligand.…”
Section: Suzuki-miyaura Cross-coupling Using Catmentioning
confidence: 99%
See 2 more Smart Citations
“…In a collaborative effort with the Serrano group, PTA based palladium complexes were synthesized and screened for the catalytic cross-coupling of nucleoside in water. In this study, the first set of [Pd(imidate) 2 (PTA) 2 ] were synthesized and found to exhibit appreciable water-solubility (110 mg/mL) [37,51]. The titled complexes can be easily synthesized by the reaction between trans-[Pd(imidate) 2 (SMe 2 ) 2 ] and PTA ligand.…”
Section: Suzuki-miyaura Cross-coupling Using Catmentioning
confidence: 99%
“…Optimization of process for the Heck reaction between 5-IdU and acrylate revealed the necessity of acetonitrile as the solvent, possibly due to the low solubility of the alkene counterpart. Using the optimal reaction conditions, nine different examples for the alkenylation of 2'-deoxyuridine analogs were obtained while the same conditions were also found to be useful in catalyzing Heck alkenylation on 5-iodo-2'-deoxycytidine (Scheme 3) [51].…”
Section: Heck Alkenylation Using Catmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has over the years developed more efficient palladium-based catalytic systems involving caged phosphine ligands such as triazaphosphaadamantane (PTA) and its derivatives (PTABS and PTAPS). 30 These ligand systems either as complexes of palladium (e.g., PTA complexes such as [Pd(Sacc) 2 (PTA) 2 ] Cat 2 or [Pd(Mal) 2 (PTA) 2 ] Cat 3 shown in Figure 1) [31][32][33] or in situ activation with a palladium precursor [PTABS with Pd(OAc) 2 ] 34 have been effective in catalyzing the modification of nucleosides (Suzuki-Miyaura, Heck alkenylation, Sonogashira coupling, aminocarbonylation) 30,35 as well as the functionalization of chloroheteroarenes (amination, etherification, and thioetherification). [36][37][38] In 2015, utilization of [Pd(Sacc) 2 (PTA) 2 ] catalytic system in catalyzing the Heck alkenylation at 1.0 mol% concentration for 5′-O-DMTr-5-iodo-2′-deoxyuridine failed…”
Section: Figure 1 Catalytic Systems Used For Cross-coupling Reactionsmentioning
confidence: 99%
“…The usefulness of PTABS as caged phosphine ligand in palladium-catalyzed cross-coupling reactions was first demonstrated by our group for a variety of applications. [32][33][34][35] Small-scale synthesis of zwitterionic ligand was accomplished by the reaction of 1,3,5-triaza-7-phosphaadamantane (PTA) with 1,4-butanesultone (Scheme 3). 34 Therefore to achieve the large-scale synthesis of PTABS, PTA would be required on a multigram scale.…”
Section: Optimization and Scale-up Of Ptabsmentioning
confidence: 99%